2013
DOI: 10.1210/jc.2012-4016
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Abnormalities in Girls and Adolescents With Turner Syndrome

Abstract: Context:Turner syndrome (TS) is a chromosomal disorder occurring in approximately 1 in 2500 live births. Individuals with TS report lower levels of physical activity than healthy control (HC) subjects. Cardiorespiratory limitations may contribute to the observed reduction in physical activity.Objective: The objective of this study was to compare muscle metabolism of patients with TS vs HC subjects before and after exercise using exercise testing, magnetic resonance imaging, and magnetic resonance spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 33 publications
4
26
0
3
Order By: Relevance
“…Another study reported a greater decrease in pH and higher ATP production after standardized workload in patients with TS as compared with healthy controls, suggesting larger stress to their skeletal muscle system. However, the recovery metabolism was similar to healthy controls, suggesting adequate muscle cell function in TS . The present study supports the hypothesis that muscle cell function is normal in TS as F max was not different from healthy girls.…”
Section: Discussionsupporting
confidence: 86%
“…Another study reported a greater decrease in pH and higher ATP production after standardized workload in patients with TS as compared with healthy controls, suggesting larger stress to their skeletal muscle system. However, the recovery metabolism was similar to healthy controls, suggesting adequate muscle cell function in TS . The present study supports the hypothesis that muscle cell function is normal in TS as F max was not different from healthy girls.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, women with Turner syndrome are characterized by increased size of type IIa muscle fibers in addition to impaired glucose tolerance and insulin resistance, indicating diminished oxygen and substrate supply for metabolic processes (Gravholt et al, 2001). It is also reported that Turner syndrome women have increased anaerobic glycolysis and lactic acid production during exercise, compared to a control group (Wells et al, 2013). …”
Section: Discussionmentioning
confidence: 98%
“…We also found the increased score for fatigue to be correlated with high stress scores, and this was not sufficiently explained by any physical comorbidities. In literature, it has been suggested that women with TS exhibit greater anaerobic stress during exercise, leading to increased muscle fatigue . Also, menopausal symptom may affect fatigue in TS women.…”
Section: Discussionmentioning
confidence: 99%